Impacts of Vinyl Group on the Diffusion and Thermal Properties of Branched Silicon-Containing Arylacetylene Resins by Molecular Dynamics Simulations - Hui Li; Zijian Sun; Lei Yang; Weihua Zhu (Molecules)
Branched-structure polyarylacetylene resins with low curing temperatures and excellent thermal stability are promising candidates for high-performance resin-matrix composites. In this work, the effects of different vinyl/acetylene group ratios on the thermal properties of star-shaped silicon-containing arylacetylene (SSA) resins and branched silicon-containing arylacetylene (BSA) resins were investigated by molecular dynamics simulations. The calculated interaction energies, diffusion behaviors, and glass transition temperatures (Tg) indicated that an increase in the vinyl/acetylene group ratio positively affected the rheological and thermal properties of the branched resins. After the introduction of the vinyl groups, the Tg value of SSA2 was greater than that of SSA0. An energy decomposition approach (EDA) analysis further confirmed that the involvement of the vinyl groups in the BSA and SSA resins provided larger interaction energies dominated by dispersion effects, leading to better thermal performance. This work may provide us with a deep understanding of the incorporation of vinyl groups in silicon-containing arylacetylene resins.